Characterization of glial-restricted precursors from rhesus monkey embryonic stem cells - Chen, Hongwei (Transl Neurosci, 2015)
Glial-restricted precursor (GRP) cells, the earliest glial progenitors for both astrocytes and oligodendrocytes, have been derived from embryos and embryonic stem cells (ESC) in rodents. However, knowledge regarding the equivalent cell type in primates is limited due to restrictions imposed by ethics and resources. Here we report successful derivation and characterization of primate GRP cells from rhesus monkey ESC. The purified monkey GRP cells were A(2)B(5)-positive and FGF2-dependent for survival and proliferation. The differentiation assays indicated that they were tri-potential in vitro and bi-potential in vivo. These newly purified GRP cells will help to facilitate understanding of the molecular mechanism of glial development in primates as well as provide a source of therapeutic donor cells for use in neuroregenerative medicine.